Efficient synthesis of fully renewable, furfural-derived building blocks via formal Diels-Alder cycloaddition of atypical addends - Cioc, Răzvan C; Harsevoort, Eva; Lutz, Martin; Bruijnincx, Pieter C A (Green chemistry : an international journal and green chemistry resource : GC, 2023)
Diels-Alder (DA) cycloaddition of furanics is emerging as a key transformation in circular chemistry, providing access to highly versatile, biobased platform molecules. Further development of this technology into viable industrial applications faces major challenges, a notorious one being the lack of reactivity of the most readily available furans, i.e. the furfural derivatives. Herein we describe the remarkably-facile intramolecular DA reaction of allyl acetals of different furfurals to efficiently afford formal DA adducts with the atypical, unreactive dienophile allyl alcohol. Our methodology gives access to unprecedented oxanorbornene derivatives in high chemo-, regio- and stereoselectivity, which can be readily diversified into valuable products. This offers the potential of scalable production of renewable chemical building blocks from cheap, bioderived platform molecules.Diels-Alder (DA) cycloaddition of furanics is emerging as a key transformation in circular chemistry, providing access to highly versatile, biobased platform molecules. Further development of this technology into viable industrial applications faces major challenges, a notorious one being the lack of reactivity of the most readily available furans, i.e. the furfural derivatives. Herein we describe the remarkably-facile intramolecular DA reaction of allyl acetals of different furfurals to efficiently afford formal DA adducts with the atypical, unreactive dienophile allyl alcohol. Our methodology gives access to unprecedented oxanorbornene derivatives in high chemo-, regio- and stereoselectivity, which can be readily diversified into valuable products. This offers the potential of scalable production of renewable chemical building blocks from cheap, bioderived platform molecules.